Endocytosis regulates TDP-43 toxicity and turnover - Guangbo Liu (Nature Portfolio, 2017)
Impaired turnover of TDP-43 by impaired autophagy or proteasomal function have been suggested to be the cause of TDP-43 accumulation, a hallmark of ALS. Here the authors demonstrate that endocytosis is also important for regulating TDP-43 turnover and toxicity.